2018
DOI: 10.1093/jhps/hny038
|View full text |Cite
|
Sign up to set email alerts
|

Previous failed hip arthroscopy negatively impacts early patient-reported outcomes of the periacetabular osteotomy: an ANCHOR Matched Cohort Study

Abstract: Surgical treatment of hip dysplasia by arthroscopic procedures remains controversial. The aim of this study was to compare outcomes of periacetabular osteotomy (PAO) after failed hip arthroscopy to a matched-control group without previous arthroscopy. Fifty-two patients who underwent PAO after failed hip arthroscopy were matched to two subjects without arthroscopy based on age, sex, BMI and radiographic severity. Pre- and post-operative patient self-reported outcomes and radiographic parameters were compared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…In contrast to other reports [ 41 , 42 ], our study indicates that hip arthroscopy can achieve successful results in patients with borderline dysplasia, who later have additional PAO surgery and support that borderline dysplastic girls have an increased risk of PAO after hip arthroscopy [ 43 ].…”
Section: Discussionsupporting
confidence: 55%
“…In contrast to other reports [ 41 , 42 ], our study indicates that hip arthroscopy can achieve successful results in patients with borderline dysplasia, who later have additional PAO surgery and support that borderline dysplastic girls have an increased risk of PAO after hip arthroscopy [ 43 ].…”
Section: Discussionsupporting
confidence: 55%
“…The most appropriate surgical treatment for different acetabular deformities is still subject of debate. More specifically, there is no consensus how to best surgically correct borderline dysplastic hips [2,37] and hips with pincer FAI secondary to acetabular retroversion [19,53,67] and overcoverage [7,18,29]. This may be related to the fact that surgical planning relies on the radiographic anatomy of the acetabulum which is affected by the acquisition technique and can only estimate the size of the weightbearing cartilage surface area [55,57].…”
Section: Discussionmentioning
confidence: 99%
“…The accurate prediction of patients who are likely to progress to PAO after hip arthroscopy is of particular interest because of the trend toward inferior outcomes in patients who undergo PAO after failed hip arthroscopy as compared with patients who initially undergo PAO alone. 21,31 Specifically, dysplasia has been a commonly implicated factor in the progression to PAO after hip arthroscopy, and patients with acetabular retroversion have demonstrated less improvement from hip arthroscopy than others with borderline dysplasia. 34,40 A cohort study of 16 patients with borderline dysplasia and excessive femoral anteversion demonstrated improvements after hip arthroscopy, although results were inferior to those of the matched control group, suggesting the possible need for PAO or femoral osteotomy in these patients.…”
Section: Discussionmentioning
confidence: 99%